2014
DOI: 10.1073/pnas.1409692111
|View full text |Cite
|
Sign up to set email alerts
|

Respiration triggers heme transfer from cytochrome c peroxidase to catalase in yeast mitochondria

Abstract: Significance We provide to our knowledge the first in vivo and in vitro evidence for H 2 O 2 -triggered heme transfer between proteins. Specifically, H 2 O 2 binds to and labilizes cytochrome c peroxidase (Ccp1)’s heme by oxidizing the proximal Fe ligand (His175), which activates Ccp1 to transfer its heme to apoCta1, and apoCcp1 subsequently escapes from mitochondria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 53 publications
3
67
0
1
Order By: Relevance
“…Recombinant Ccp1 with MI at positions –2 and –1 of the mature protein was overexpressed as the apoprotein in BL21(DE3) cells, purified and reconstituted with hemin as described previously. 14 Suppliers of (bio)chemicals were as follows: Coomassie (MP Biomedicals); hemin chloride, HPLC grade acetonitrile, diethylenetriamine-pentaacetic acid (DTPA) (Sigma Aldrich); and 30% hydrogen peroxide (Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant Ccp1 with MI at positions –2 and –1 of the mature protein was overexpressed as the apoprotein in BL21(DE3) cells, purified and reconstituted with hemin as described previously. 14 Suppliers of (bio)chemicals were as follows: Coomassie (MP Biomedicals); hemin chloride, HPLC grade acetonitrile, diethylenetriamine-pentaacetic acid (DTPA) (Sigma Aldrich); and 30% hydrogen peroxide (Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…32 The CCP activity of oxidized Ccp1 was determined by monitoring the oxidation of horse heart Cyc II by H 2 O 2 as reported. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptic peptides were obtained by resolving TyrA preparations by SDS-PAGE, excising appropriate regions from the gel and then performing trypsin proteolysis on each sample as outlined previously (Shevchenko et al 1996). The resulting peptides were resuspended in 15-50 µL of solubilization solution containing 2 % acetonitrile (ACN) and 1 % of formic acid (FA) and processed by LC-MS/MS as described previously (Kathiresan et al 2014). MS/MS fragments were analyzed using the Thermo Proteome Discoverer software (v1.3) with the SEQUEST search engine with mass filters for the oxidation of methionine (+15.995 Da) and for the alkylation of cysteine (+57.021 Da).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Very recently, we reported that signaling by endogenous, respiration-derived H 2 O 2 involves transfer of Ccp1's heme to mitochondrial/peroxisomal catalase A [23,59]. The strength of this signaling regulates life span by limiting the protective H 2 O 2 -induced mitohormesis response of the cell [47].…”
Section: The Response Of Cells To Exogenous Onoo(h) Challenge Is Ccp1mentioning
confidence: 99%